ROLE MODEL FOR EDUCATORS AS AN ALTERNATIVE IN THE ESTABLISHMENT OF ISLAMIC CHARACTER - Samsul Arifin; Eva Maghfiroh (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
The role of educators in Islamic religious education (PAI) is very important for the formation of the character of students in madrasas. Therefore, an educator must be able to set a good example. Educators are role models for their students. Strengthening character in the context of education is an important factor in the ongoing part of the education system. This relates to the direct interaction of educators with their students, where students will see, hear and feel directly what is taught by educators, following the philosophy of the educators themselves, which is defined as someone who is "guided and imitated." This research uses a qualitative-descriptive method with a case study approach. Data collection techniques were carried out by conducting in-depth interviews, observation, and documentation. This research shows that role educators are role models in realizing the character and mental education. The role of character and mental education in the education system must be the foundation of other education because science and adab are continuous; if science is not accompanied by adab, then that knowledge will have no benefits and will not be blessed it could be that knowledge. It will be used for something false and evil. Peran Tenaga pendidik di lingkungan Pendidikan Agama slam (PAI) sangatlah penting bagi Pembentukan karakter peserta didik di madrasah. Oleh karena tu seorang tenaga pendidik haruslah dapat memberikan teladan baik. Tenaga pendidik menjadi suri teladan (Role model) bagi peserta didiknya. Penguatan karakter dalam konteks pendidikan merupakan faktor penting dari bagian sistem pendidikan yang sedang berlangsung. Hal ni berkenaan dengan nteraksi tenaga pendidik secara langsung terhadap peserta didiknya, dimana peserta didik akan melihat, mendengar serta merasakan secara langsung apa saja yang diajarkan oleh tenaga pendidik, sesuai dengan filsafat dari tenaga pendidik tu sendiri yang diartikan sebagai seorang yang “ digugu dan ditiru”. Penelitian ni menggunakan metode kualitatif – dekskriptif, dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan dengan melakukan wawancara mendalam, observasi, dan dokumentasi. Penelitian ni menghasilkan bawah peran tenaga pendidik memposisikan dirinya sebagai seorang yang menjadi panutan dan suri teladan dalam mewujudkan pendidikan karakter serta mental. Peranan pendidikan karakter dan mental dalam sistem pendidikan haruslah menjadi pondasi dari pendidikan yang lain karena sejatinya lmu serta adab menjadi sesuatu yang berkisanambungan, jika sebuah lmu tanpa di sertai dengan adab, maka lmu tersebut tidak akan memiliki manfaat serta tidak barokah, dan bisa jadi lmu tersebut akan digunakan untuk sesuatu hal yang bathil dan munkar.